Usługi sieciowe - podstawy technologiczne oraz przykłady zastosowań w przedsiębiorstwach - Rot, Artur (Web Services: Technological Basis and the Examples of Application in Enterprises, 2007)
Web services are often defined as software systems designed to support interoperable machine--to-machine interaction over a network. They are Web-based enterprise applications that use open, XML-based standards and transport protocols to exchange data with calling clients. Web services enable the new generation of Internet-based applications. These services support application-to--application Internet communication, so that applications at different network locations can be integrated as if they were part of a single, large software system. Several key standards have emerged that together form the foundation for web services: XML (Extensible Markup Language), WSDL (Web Services Definition Language), SOAP (Simple Object Access Protocol) and UDDI (Universal Description, Discovery, and Integration). In addition, ebXML (Electronic Business XML) has been specified to facilitate automated business process integration among trading partners. The technology, architecture and those key standards have been described in the article. The paper presents also examples and major benefits of application of this technology in enterprises.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (10); 2007; nr 1150, s. 159-170